PENGARUH JUMLAH KUMPARAN ROTOR MESIN SEREMPAK KUTUB TIDAK MENONJOL TERHADAP DISTRIBUSI FLUKS MEDAN ELEKTROMAGNIT - Saffira, Constantine
Abstract : Magnetic flux density were calculated analytically for synchronous machine non salient pole, with distributed coil arranged linierly. The analytical calculation utilized magnetic potensial vector equation. In effort to determine the flux density, separating variable method, continuoe Fourier series approximation and Gauss and Ampere laws were to solve the equation, to calculate current sheet and to determine boundary condition, accodingly. The result were presented in magnetic flux density against a number of coil machine.